2019
DOI: 10.1002/aenm.201901566
|View full text |Cite
|
Sign up to set email alerts
|

The Spacer Cations Interplay for Efficient and Stable Layered 2D Perovskite Solar Cells

Abstract: Organic spacer cations in layered 2D (A1)2(A2)n−1BnX3n+1 (where A1 is an organic cation acting as a spacer between the perovskite layers, A2 is a monovalent cation, e.g., Cs+,CH3NH3+, CH(NH2)2+) perovskite materials improve the long‐term stability of the resulting solar cells, but hamper their power conversion efficiency due to poor carrier generation/transportation. Rational guidelines are thus required to enable the design of organic spacer cations. Herein, mixed A1 cations are employed in layered 2D perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 48 publications
(57 reference statements)
4
93
0
1
Order By: Relevance
“…phenethylammonium halide (PEAX), or n-butylammonium halide (n-BAX)) and the salts of a 3D perovskite (e.g. methylammonium halide (MAX) and lead halide (PbX 2 )) have been dissolved together in a solvent or a mixed solvent 8,[14][15][16][17][18][19] . Here, unlike the conventional way, we incorporate a liquid-form neutral reagent, benzylamine (BnA) into the methylammonium lead bromide (MAPbBr 3 ) precursor to form 3D/2D hybrid perovskites 20 .…”
mentioning
confidence: 99%
“…phenethylammonium halide (PEAX), or n-butylammonium halide (n-BAX)) and the salts of a 3D perovskite (e.g. methylammonium halide (MAX) and lead halide (PbX 2 )) have been dissolved together in a solvent or a mixed solvent 8,[14][15][16][17][18][19] . Here, unlike the conventional way, we incorporate a liquid-form neutral reagent, benzylamine (BnA) into the methylammonium lead bromide (MAPbBr 3 ) precursor to form 3D/2D hybrid perovskites 20 .…”
mentioning
confidence: 99%
“…[ 96 ] In comparison with the unsaturated aromatic alkylamine cations, the chain alkylamine cations are more likely to manage the precursor assembly and promote the vertical growth orientation of RP perovskite crystals. [ 97 ] With regard to the chain of space alkylamine cations, it has been reported that space cations with shorter chain favored the high‐quality crystallization of RP perovskites. [ 76 ] Huang's group has attributed this advantage of shorter‐chain‐based space cations to the reduced steric hindrance of the perovskite during self‐assembly.…”
Section: Fundamental Understanding Of Rp Perovskites Film In Pscsmentioning
confidence: 99%
“…Figure a–d displays the RP perovskite film formation process based on GA + and PEA + as a second space cation. [ 97,99 ] The interaction between space cations and solvents controls the evaporation rate of solvents and further influences the supersaturation and crystallization dynamics during the RP perovskite film formation process, which plays a crucial role in the crystal growth orientation. [ 68 ] All these hint that the high‐quality RP perovskite film can be achieved via appropriately tuning organic space cations, which will be discussed later in detail.…”
Section: Fundamental Understanding Of Rp Perovskites Film In Pscsmentioning
confidence: 99%
“…[157] This study highlights the importance of the stability of precursor solution, especially under illumination. Besides, partial substitution of MA + by other larger cations, such as GA + (CH 6 N 3 + ), [158] AVA + (HOOC(CH 2 ) 4 NH 3 + ), [44] BA + (C 4 H 9 NH 3 + ), [159] PEA + (C 6 H 5 (CH 2 ) 2 NH 3 + ), [160] has also proved to be an effective way to improve the stability of perovskites. [77] Although mixed cations can improve the photostability of perovskite, the organic cations may still be potentially deprotonated under intense light illumination.…”
Section: Decomposition Of Organic Cationsmentioning
confidence: 99%